2018
DOI: 10.1021/acs.macromol.8b01919
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Reactivity of Two Different Spiropyran Mechanophores in Polydimethylsiloxane

Abstract: We investigate the effect of pulling point location on the mechanochemical activation of two isomers of spiropyran in cross-linked polymeric materials through computational calculations and in situ fluorescence measurements. The threshold stress and strain required to activate the spiropyran mechanophores under tensile load are characterized. For both spiropyran isomers, applied stress favors the activated merocyanine states; however, despite differences in mechanochemical behavior predicted by quantum chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
117
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(124 citation statements)
references
References 47 publications
5
117
0
2
Order By: Relevance
“…4 In the meantime, many color-changing mechanophores and corresponding motifs which change their photoluminescence properties have been investigated. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] While the latter require auxiliary means for detection, a change of the emission color and/or intensity can often be detected more easily than an absorption color change. 22 Most of the fluorescent mechanophores reported so far, emit in the blue and green wavelength region.…”
Section: ■ Introductionmentioning
confidence: 99%
“…4 In the meantime, many color-changing mechanophores and corresponding motifs which change their photoluminescence properties have been investigated. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] While the latter require auxiliary means for detection, a change of the emission color and/or intensity can often be detected more easily than an absorption color change. 22 Most of the fluorescent mechanophores reported so far, emit in the blue and green wavelength region.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The maximum force required for scission was calculated from the slope in the energy to distance graph (see Figs. S36–40 in the SI) . These were plotted versus the mechanochemical fragmentation rates of each polymer, which were calculated from three ultrasonication experiments, where aliquots were extracted every 15 min and analyzed by triple‐detector GPC (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the intensity of mechanical stress that a polymer can be subject to, the affected molecules within the polymeric chain can induce a chemical transformation in the responsive material (i.e., mechanophores) accompanied by a change in optical properties. Mechanophores include NITEC [443] and SP [444,445] which changes color in bulk polymers from yellow to red [446], as it has preferential mechanochemical activation in the stress direction [447]. Aside from mechanochromic, we found that less attention has paid to other chromogenic self-diagnosis and report strategies, particularly, the thermo-and electrochromic.…”
Section: Self-diagnosis and Reportingmentioning
confidence: 95%